Predictors of Ischemic and Hemorrhagic Strokes Among People Living With HIV: The D:A:D International Prospective Multicohort Study. (August 2019) - Hatleberg, Camilla Ingrid; Ryom, Lene; Kamara, David; De Wit, Stephane; Law, Matthew; Phillips, Andrew; Reiss, Peter; D'Arminio Monforte, Antonella; Mocroft, Amanda; Pradier, Christian; Kirk, Ole; Kovari, Helen; et al.
Abstract: Background: Hypertension is a stronger predictor of hemorrhagic than ischemic strokes in the general population. We aimed to identify whether hypertension or other risk factors, including HIV-related factors, differ in their associations with stroke subtypes in people living with HIV (PLWHIV). Methods: HIV-1-positive individuals from the Data collection on Adverse events of anti-HIV Drugs (D:A:D) study were followed from the time of first blood pressure (BP) measurement after 1/1/1999 or study entry until the first of a validated stroke, 6 months after last follow-up or 1/2/2014. Stroke events were centrally validated using standardized criteria. Hypertension was defined as one systolic BP ≥ 140 mm Hg and/or diastolic BP ≥ 90 mm Hg. Poisson and Cox proportional hazards regression models determined associations of established cerebro/cardiovascular disease and HIV-related risk factors with stroke and tested whether these differed by stroke subtype. Findings: 590 strokes (83 hemorrhagic, 296 ischemic, 211 unknown) occurred over 339, 979 person-years (PYRS) (incidence rate/1000 PYRS 1.74 [95% confidence interval (CI) 1.60–1.88]). Common predictors of both hemorrhagic and ischemic strokes were hypertension (relative hazard 3.55 [95% CI 2.29–5.50] and 2.24 [1.77–2.84] respectively) and older age (1.28 [1.17–1.39] and 1.19 [1.12–1.25]). Male gender (1.62 [1.14–2.31] and 0.60 [0.35–0.91]), previous cardiovascular events (4.03 [2.91–5.57] and 1.44 [0.66–3.16]) and smoking (1.90 [1.41–2.56] and 1.08 [0.68–1.71]) were stronger predictors of ischemic then hemorrhagic strokes, whereas hypertension, hepatitis C (1.32 [0.72–2.40] and 0.46 [0.30–0.70]) and estimated glomerular filtration rate < 60 mL/min/1.72 m 3 (4.80 [2.47–9.36] and 1.04 [0.67–1.60]) were stronger predictors of hemorrhagic than ischemic strokes. A CD4 count < 200 cells/μL was associated with an increased risk of hemorrhagic stroke only. Interpretation: Risk factors for stroke may differ by subtype in PLWHIV, emphasizing the importance of further research to increase the precision of stroke risk estimation.